Land (Symphony in the Flint Hills, 2014)
Natural history is the heart and soul of the Flint Hills. The terraced landscape created by layers of limestone, flint, and shale; the seasonally changing colors of bluestem, Indian, and switch grasses; the wildlife and the streams and ponds are all evoked by the writers in this section. This is the introduction to the, "Land," section of the Field Journal.
Keywords: land; Flint Hills; grassland; prairie; nature; natural; native; bluestem; animals